EQUIVALENTS OF THE PASSIVE EIGHT-EARTH POLAR WITH THREE INPUT AND FIVE OUTPUT CONCLUSIONS - G. A. Bolshanyn (Известия высших учебных заведений: Проблемы энергетики, 2019)
Eight-poles of various designs, including an eight-terminal network with three input and five output terminals, are needed to replace some power objects. Especially when only the input and output characteristics of electrical energy are of interest. The paper presents the eightterminal network equations with three input and five output terminals, establishing a connection between these characteristics. Equations of the A-form establish a connection between the input and output voltages and currents; the B-form equations establish a connection between the output and input voltages and currents; G-form equations establish a connection between the input current, output voltages and output voltage, output currents; H-form equations establish the relationship between the input voltage, output currents and output current, output voltages; the Yform equations establish a connection between the input and output currents and the input and output voltages; The Z-form equations establish the relationship between the input and output voltages and the input and output currents. When implementing these equations, attention should be paid to the difference in the directions of the currents in each individual case.